2022
DOI: 10.3390/vetsci9100551
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Diagnosis of Hereditary Gastrointestinal Polyposis in Jack Russell Terriers

Abstract: Hereditary GI polyposis in JRTs is a novel hereditary disease characterized by the development of solitary and multiple polypoid tumors, predominantly in the stomach and/or colorectum. Our recent study indicated that JRTs with GI neoplastic polyps harbor an identical germline variant in the APC gene, c.[462_463delinsTT], in a heterozygous state. Unlike sporadic cases, dogs afflicted with hereditary GI polyposis can be expected to have a prolonged survival time, as hereditary tumors are noninvasive. Since the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
2
6
0
1
Order By: Relevance
“…17 Unlike miniature Dachshunds or Jack Russell Terriers in Japan, Dachshunds and Jack Russell Terriers of our cohort were not found to be overrepresented. 20,26,27 Hematochezia, rectal bleeding or both abnormalities were consistently reported in this study, a similar finding to that reported in a study on colorectal adenocarcinomas in dogs. 19 However, diarrhea was only present in one quarter of the dogs.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…17 Unlike miniature Dachshunds or Jack Russell Terriers in Japan, Dachshunds and Jack Russell Terriers of our cohort were not found to be overrepresented. 20,26,27 Hematochezia, rectal bleeding or both abnormalities were consistently reported in this study, a similar finding to that reported in a study on colorectal adenocarcinomas in dogs. 19 However, diarrhea was only present in one quarter of the dogs.…”
Section: Discussionsupporting
confidence: 92%
“…We found that West Highland White Terriers were overrepresented among dogs with colorectal polyps, which was already suggested in a previous study, although this finding was solely based on the percentage of dogs of the breed among the diseased cohort 17 . Unlike miniature Dachshunds or Jack Russell Terriers in Japan, Dachshunds and Jack Russell Terriers of our cohort were not found to be overrepresented 20,26,27 …”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In JRTs, this hereditary disease is characterized by the development of solitary and multiple polyps in the stomach and large intestine, with a predilection for the gastric antrum and rectum; multiple lesions can develop simultaneously at both locations [ 7 , 14 ]. Most lesions are histopathologically diagnosed as adenomas or adenocarcinomas [ 7 , 14 ]. Initial GI lesions can arise at variable ages, reportedly between 2 and above 10 years and at an average age of 7.7 years [ 7 ].…”
Section: Introductionmentioning
confidence: 99%